Exploring Online Synthesis for CGRAs with Specialized Operator Sets. (22nd June 2011) - Döbrich, Stefan; Hochberger, Christian
Abstract : The design of energy-efficient systems has become a major challenge for engineers over the last decade. One way to save energy is to spread out computations in space rather than in time (as traditional processors do). Unfortunately, this requires to design specialized hardware for each application. Also, the nonrecurring expenses for the manufacturing of chips continuously grow. Implementing the computations on FPGAs and CGRAs solves this dilemma, as the non recurring expenses are shared between many different applications. We believe that online synthesis that takes place during the execution of an application is one way to broaden the applicability of reconfigurable architectures as no expert knowledge of synthesis and technologies is required. In this paper, we give a detailed analysis of the amount and specialization of resources in a CGRA that are required to grant a significant speedup of Java bytecode. In fact, we show that even a relatively small number of specialized reconfigurable resources is sufficient to speed up applications considerably. Particularly, we look at the number of dedicated multipliers and dividers. Also, we discuss the required number of concurrent memory access operations inside the CGRA. Again, it shows that two concurrent memory access operations are sufficient for almost all applications.